Sustaining participation in irrigation systems of Ethiopia: what have we learned about water user associations? - Yami, Mastewal (IWA Publishing, 2013)
Community participation, defined as engaging users of schemes in the decision-making processes for the planning and implementation of irrigation projects, is critical for the sustainability of irrigation schemes. This study was carried out in three regional states of Ethiopia to investigate the contribution of Water User Associations (WUAs) to sustaining participation in irrigation projects. The paper demonstrates that the poor understanding of community participation and institutional development by project staff in donor-supported irrigation projects results in the poor performance of WUAs in enhancing participation in irrigation systems. The interventions of external bodies in setting up the WUA by-laws and in determining the responsibilities of users and WUA committees contributed to the low level of participation. The transfer of schemes to WUAs without building WUA committees' abilities in operation and maintenance constrained their ability to sustainably manage irrigation schemes. The WUA committees are male-dominated and the views of women are hardly represented in the decision-making. Therefore, establishing WUA committees that reflect the interests and inputs of scheme users is crucial to achieve fair decision-making. Local authorities and non-governmental organizations could do more to change perceptions and behavior on the importance of gender equity in sustaining the positive outcomes of irrigation at household and community levels.